Pengaruh Current Ratio, Debt to Equity Ratio, dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2021 - Nabila Utami Dewi; Endang Taufiqurahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine, analyze, and describe the effect of Current Ratio, Debt To Equity Ratio, and Earnings Per Share on Stock Prices of Manufacturing Companies in the Automotive Sub-Sector and Components Listed on the Indonesia Stock Exchange for the 2016- 2021 Period. This research uses verification descriptive analysis method and uses multiple linear regression analysis tools. The research population was 13 companies and the sampling technique used purposive sampling technique was 5 companies in a period of 6 years with a total of 30 samples. The results of this study indicate that the current ratio partially has no significant effect on stock prices, the debt to equity ratio partially has a negative effect on stock prices, and earnings per share partially has a significant effect on stock prices. While the results of the study simultaneously resulted that CR, DER, and EPS had a significant effect on stock prices.